1987
DOI: 10.1055/s-0028-1082437
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Measurement: The Impact of Communication Augmentation

Abstract: Harris3 conducted the first microanalytic study of the conversational communication interaction behaviors of primary communication partners and selected subjects fitted with augmentative communication techniques. Gradually, additional similar studies have been reported, typically utilizing videoanalysis. These studies have focused on communication rate, density, intelligibility, mode, functions, discourse, and, to a lesser degree, on communication training procedures, attitudes, and ~trategies.~ Results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…If the cognitive load is too great and the users' operational skills suffer as a result, their overall communicative competence will be impaired. Buzolich and Higginbotham (1985) and Culp (1987) have suggested that an individual's operational competence may be evaluated best in terms of the accuracy and speed with which messages are formulated. A certain level of accuracy and speed of system use is required to communicate effectively; however, proficiency in system operation does not, in and of itself, ensure functional use (Kraat, 1984).…”
Section: Operational Competencementioning
confidence: 99%
“…If the cognitive load is too great and the users' operational skills suffer as a result, their overall communicative competence will be impaired. Buzolich and Higginbotham (1985) and Culp (1987) have suggested that an individual's operational competence may be evaluated best in terms of the accuracy and speed with which messages are formulated. A certain level of accuracy and speed of system use is required to communicate effectively; however, proficiency in system operation does not, in and of itself, ensure functional use (Kraat, 1984).…”
Section: Operational Competencementioning
confidence: 99%